THE TRANSNATIONALIZATION OF IDEAS: THE COUNTER-SUBVERSIVE SCHOOL FROM ARGENTINA TO GUATEMALA - Rostica, Julieta Carla (2018)
The article aims to demonstrate the flow and reception of ideas related to national security from Argentina to Guatemala as another form of transnationalization of State terrorism in Latin America, and provide another example of the Argentine collaboration in the counter-subversive fight in Guatemala. We will study, in particular, the reception of Argentina’s ideas in the Guatemala’s Manual de Guerra Contrasubversiva (MGC) at the end of the seventies: the Osiris Villegas book, Guerra revolucionaria comunista and argentina army’s pamphlet, Instrucciones para lucha contra la subversión, both dated in 1962. Moreover, the article will make an approximation to these sources, to their authors, to the context of their production and, above all, to their ideas. Finally, the main ideas received in the MGC are systematized, the same that the Guatemalan army used during the period that perpetrated the highest number of human rights violations (1978-1985).